Prevalence of women's violence against men in Peru: associated factors and trend evaluation between the years 2018-2022 - Coronel-Moreno, Shearly Katherin (2025)
Objective: To determine the prevalence of violence perpetrated by women against men, as well as the associated factors, and its trend over period 2018 to 2022. Materials and methods: An observational, analytical, trend-based study was conducted using secondary data from the Demographic and Family Health Survey of Peru. The annual prevalence of violence was estimated according to characteristics of the women, their partners, and the households. Binary logistic regression models were employed to identify associated factors, and joinpoint regression models were used to assess changes in trend. Results: The prevalence of violence perpetrated by women against men was 3.5% in 2018, decreasing progressively over time: 3.2% in 2019, 2.8% in 2020, and 2.4% in both 2021 and 2022, reflecting an annual percentage change of –9.9% (IC95%: –13.9- –5.7). likelihood of perpetrating violence decreased with the woman’s age and in households located in rural areas or outside the capital. Conversely, the absence of children, age disparity between spouses, higher wealth index, and prior experience of any form of violence were associated with an increased risk of perpetration. Conclusions: A significant decline was observed in the prevalence of violence perpetrated by women against men, from 3.5% in 2018 to 2.4% in 2022. Associated factors included age difference between partners, presence of children, urban residence, and prior victimization across all forms of violence.